Perawatan Perikoronitis Regio Molar Satu Kanan Bawah pada Anak Laki-Laki Usia 6 Tahun - Laily Kadaryati; Ike Siti Indiarti (Faculty of Dentistry, Universitas Indonesia, 2015)
Pericoronitis is non specific infection at gingival around the crown of the tooth which imperfect eruption. Clinical appearance of pericoronitis is reddish and refined swelling at the gingival around the tooth that involved with disseminating of painful extend to ear, throat and mouth base. Many effects caused by pericoronitis such as unpleasant feeling caused of pain when chewing and occlusion, come out of purulent exudates from the edge of the gingival, and also can finded cheek swollen and lymphadenitis. The management of pericoronitis consists of infection control phase and tooth extraction based on indication or removing of operculum tissue that covered the tooth. This paper reported a 6 years old boy that coming with complaint of gusi rahang bawah belakang kanan terasa bengkak dan mengganggu. The treatment that be done is excision of the operculum tissue.